Conception of an Ovarian Heterotopic Pregnancy - Shahina Ishtiaque; Tahseen Qadir; Marvi Farooqui (ziauddin University, 2024)
ABSTRACT Spontaneous heterotopic pregnancy is a rare clinical condition in which intrauterine and extrauterine pregnancies occur at the same time. The occurrence of an ovarian heterotopic pregnancy is a rare singular event comprising only 2.3% of all heterotopic pregnancies, extremely rare among naturally conceiving women. We present a case of a 30-year old patient with a spontaneously conceived heterotopic pregnancy. The patient was admitted to our hospital with left iliac fossa pain and amenorrhea. A transvaginal ultrasound scan showed an ovarian and an intrauterine heterotopic pregnancy. A laparotomy with left oophorectomy was performed at 10 weeks of gestation. The patient was followed up on regular antenatal visits. A healthy baby was delivered via spontaneous vaginal delivery at 38 weeks. Heterotopic pregnancy can occur in women of reproductive age in the absence of any predisposing risk factor; only with an early diagnosis and treatment the intrauterine pregnancy will reach viability with a greater chance of a favorable obstetric outcome. KEY WORDS: Spontaneous Conception, Adnexal Mass, Heterotopic Pregnancy.